Immigration, Religion, and Gender in the Lives and Work of Selma Stern, Hannah Arendt, and Toni Oelsner - Julie L. Mell (Religions)
This article examines the intersection of immigration, religion, and gender in the lives and writings of Selma Stern, Hannah Arendt, and Toni Oelsner. It highlights how their lives were shaped by immigration and circumscribed by the unfinished movement towards both Jewish emancipation and women’s emancipation. These three German–Jewish women immigrated from Nazi Germany to the US, where they lived much or all of their adult life. All three belonged to the first generation of German women entering the academy. And all produced path-breaking works that contested antisemitism. In these works, the concepts of the Court Jew and the Jewish economic function loom large. This article will focus on how each constructed, transformed, or critiqued the Jewish economic function within the context of their larger intellectual trajectory and their biographies. The similarities and differences between them illustrate the range of possibilities open for immigrants who were women, who were Jewish, and who were German to integrate into American academic life. In so doing, this article aims to contribute to the study of gender in immigration, as well as to Jewish intellectual history, and the history of Jewish émigrés.